Evaluating water resources carrying capacity of Pearl River Delta by entropy weight-TOPSIS model - Zhou, Yueying; Liu, Zufa; Zhang, Bowei; Yang, Qiannan (Frontiers in Environmental Science, 2022)
To understand the spatio-temporal changes in the water resources carrying capacity (WRCC) of Pearl River Delta (PRD), 19 indicators were selected from three subsystems (water resources, socio-economic, and eco-environment), and the entropy weight-TOPSIS model was employed to analyze the WRCC of each cities in PRD from 2015 to 2020. As the result shows, the water resources subsystem had the largest weight in the evaluation system, followed by the socio-economic subsystem, and the eco-environmental subsystem; among these indicators, economic density, water resources per capita, annual precipitation, and new soil erosion treatment area had the highest weights; the PRD had a low WRCC score overall, with considerable regional differences; the capacity score changed with time, but the ranking of cities remained largely the same, with Shenzhen, Zhaoqing, and Huizhou marking higher scores, whereas Zhongshan, Foshan, and Zhuhai achieving lower scores. It was also found that Shenzhen had a high score for the socio-economic subsystem, which made up for the shortage of natural water resources there; cities like Huizhou, Jiangmen, and Zhaoqing which boast rich water resources and extensive development achieved high scores for the water resource subsystem and eco-environmental subsystem. As the PRD develops, it is important to optimize dispatch of water resources, boost green economy, and promote ecological wellbeing.